2016
DOI: 10.1016/j.bpj.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Forced Unfolding Mechanism of Bacteriorhodopsin as Revealed by Coarse-Grained Molecular Dynamics

Abstract: Developments in atomic force microscopy have opened up a new path toward single-molecular phenomena; in particular, during the process of pulling a membrane protein out of a lipid bilayer. However, the characteristic features of the force-distance (F-D) curve of a bacteriorhodopsin in purple membrane, for instance, have not yet been fully elucidated in terms of physicochemical principles. To address the issue, we performed a computer simulation of bacteriorhodopsin with, to our knowledge, a novel coarse-graine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
(87 reference statements)
2
7
0
Order By: Relevance
“…One all-atom MD study (17) identified a number of key residues that resist mechanical unfolding in the intermediate states probed by the experiment (11), although its pulling speed (1-50 m/s) was too fast to observe WLC behavior for the unfolded segments. A 2016 CG study used the same pulling rate as ours ($10 6 nm/s) and found WLC behavior (20). Although many features are similar between this and our studies, we observed more intermediates (Table S2).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…One all-atom MD study (17) identified a number of key residues that resist mechanical unfolding in the intermediate states probed by the experiment (11), although its pulling speed (1-50 m/s) was too fast to observe WLC behavior for the unfolded segments. A 2016 CG study used the same pulling rate as ours ($10 6 nm/s) and found WLC behavior (20). Although many features are similar between this and our studies, we observed more intermediates (Table S2).…”
Section: Discussionsupporting
confidence: 82%
“…These methods have been proven beneficial in detecting sparsely populated intermediates and elucidating unfolding pathways of soluble (2)(3)(4)(5) and membrane proteins (6)(7)(8)(9)(10)(11)(12)(13)(14). Simulations and theory have aided the experimental SMFS studies by revealing the complexity of the folding process (15)(16)(17)(18)(19)(20)(21). These measurements are challenging from the computational standpoint, in part because of the demanding computation resources required to simulate the experimental timescales (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 of the supplementary material). 28 Our work also documented that ∆G 0 per nm varied more than 15-fold, from 11 kcal/mol at the top of the ED helix pair to 0.6 kcal/mol at the bottom of the same helix pair. While it has long been known that hydrophobicity of the amino-acid sequence within the lipid bilayer and inter-and intra-helix interactions contribute to this variation, 29 recent work also shows variations in the strength of hydrogen bonds within TM helices.…”
Section: Resultssupporting
confidence: 61%
“…However, the origin of such patterns has not been fully understood yet. Recently, we have developed our original program, ppfc (PolyPeptide chain Force-distance Curve simulator), to study the forced unfolding mechanism of membrane proteins [33,34], and successfully reproduced experimentally observed FD curves. The program and user's manual are available on the web site [35].…”
Section: Mechanical Unfoldingmentioning
confidence: 95%